2015
DOI: 10.1002/j.2205-0140.2015.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent median artery thrombosis: A rare cause of carpal tunnel syndrome

Abstract: Background: Carpal tunnel syndrome (CTS) is a sporadic event with compression of the median nerve (MN). Persistent median artery (PMA) thrombosis is an exceptionally rare cause of CTS. Case report: 38‐year‐old male presented with acute on subacute right wrist pain with positive Tinel's sign. An ultrasound and computed angiography study confirmed a PMA with thrombosis. The patient was treated with intravenous heparin then discharged home on enoxaparin and warfarin crossover. Discussion: PMA can lead to CTS by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
1
12
1
2
Order By: Relevance
“…Since CTS caused by occluded PMA is rare, it seems that data about clinical features of CTS caused by occluded PMA distinguished from other causes are insufficient. In a case reported by Dahmam et al [ 4 ], there was a change of temperature in hand, although this was not found in our case or other cases [ 5 , 6 ]. This difference may be dependent on the dominance of the median artery of the hand.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Since CTS caused by occluded PMA is rare, it seems that data about clinical features of CTS caused by occluded PMA distinguished from other causes are insufficient. In a case reported by Dahmam et al [ 4 ], there was a change of temperature in hand, although this was not found in our case or other cases [ 5 , 6 ]. This difference may be dependent on the dominance of the median artery of the hand.…”
Section: Discussioncontrasting
confidence: 81%
“…When patients suffer from severe acute symptoms caused by occluded PMAs, some reports recommend surgery [ 4 , 5 ]. In another report, when collateral vessels exist, conservative therapy using anti-coagulants was successful [ 6 ]. Since we confirmed the collateral’s existence by CT angiography without observing ischemic signs, we tried conservative treatment which worked well.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the PMA has been reported by a few studies and is quite variable (10%–50%, 4%, and 1.5%–27%)[ 2 ] and dependent on populations studied; out of which, a thrombosed persistent median artery causing CTS is very rare. [ 3 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals maintain their median artery throughout their lifetime without becoming symptomatic; most present as a fibrotic thread or a minuscule vessel (7). Studies have shown that a thrombosed persistent median artery can cause increased pressure within the tunnel leading to median nerve compression (8). Thrombosis is due to various etiologies such as infection, trauma, rheumatoid disease, or repetitive movements of the wrist (3).…”
Section: Discussionmentioning
confidence: 99%